Long-duration Nonthermal Motions in the Supra-arcade and Loop-top Region during an Eruptive Solar Flare - Tingyu Gou; Katharine K. Reeves (The Astrophysical Journal, 2025)
Solar flares are widely accepted to be powered by magnetic reconnection that involves complex dynamics in various scales. The flare supra-arcade and loop-top region, directly impacted by fast reconnection downflows, contains a wealth of microscopic dynamics, which are, however, difficult to resolve in imaging. We present simultaneous spectroscopic and imaging observations of hot flaring plasma above the loop tops by the Interface Region Imaging Spectrograph (IRIS) and Solar Dynamics Observatory/Atmospheric Imaging Assembly. IRIS continuously observed high-temperature Fe xxi 1354.08 Å spectral emissions throughout the long-duration gradual phase of the X-class flare. We found weak Doppler blueshifts near the loop-top region, indicative of bulk plasma motions from chromospheric evaporation based on the three-dimensional flare loop orientation. Strong nonthermal velocities are detected at the bottom of the flare supra-arcade fan/plasma sheet, suggestive of the presence of turbulence in the flare current sheet region. In addition, disorganized nonthermal plasma motions are constantly detected until the very end of the flare, indicating irregular unresolved plasma flows in the cusp and loop-top region. The spatial and temporal evolution of spectral parameters follow the dynamics resulting from ongoing magnetic reconnection during the prolonged gradual phase. The long-lasting nonthermal plasma motions may contribute to the high and steady temperature of flaring plasmas above flare loops.